2020
DOI: 10.3389/fphar.2020.01344
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast Drug May Improve COVID-19 Prognosis: A Review of Evidence

Abstract: With the lack of effective therapy, chemoprevention and vaccination, focusing on the immediate repurposing of existing drugs gives hope of curbing the pandemic. Interestingly, montelukast, a drug usually used in asthma, may be proposed as a potential adjuvant therapy in COVID-19. The aim of the present article was to review the properties of montelukast that could be beneficial in COVID-19. Ten experimentally supported properties were retrieved, either related to SARS-CoV-2 (antiviral properties, prevention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 55 publications
(59 reference statements)
0
43
0
3
Order By: Relevance
“…As outlined in the introduction, there is a current interest in repurposing of MTK for the treatment of patients with neurodegenerative diseases such as dementia patients 17,20,21 , and of COVID-19 patients 22,23 . Both show dysphagia, and therefore, a mucoadhesive film might have certain advantages.…”
Section: Resultsmentioning
confidence: 99%
“…As outlined in the introduction, there is a current interest in repurposing of MTK for the treatment of patients with neurodegenerative diseases such as dementia patients 17,20,21 , and of COVID-19 patients 22,23 . Both show dysphagia, and therefore, a mucoadhesive film might have certain advantages.…”
Section: Resultsmentioning
confidence: 99%
“… Barré et al, 2020 ; Şener et al, 2006 ; Zhang et al, 2020b .…”
Section: Uncited Referencesunclassified
“…Plus, it has been demonstrated that Montelukast can reduce neuroinflammation and induce neurogenesis by GPR17 receptor. Several studies showed that Montelukast can mitigate cytokine storms and reduce interaction between SARS-CoV-2 and ACE2, as well as increase mitochondrial mass and function at systemic level [ 278 ].…”
Section: Antioxidants As Neuroprotectors In Patients Infected With Covid-19mentioning
confidence: 99%